Ex‐post facto analysis of diseases of the Gulf of Mexico′s white shrimp Litopenaeus setiferus. Issue 5 (28th September 2012) - del, Rodolfo Enrique; Sosa‐Lopez, Atahualpa; Pech, Daniel
Abstract This study presents an Ex‐Post Facto analysis of diseases of wild juvenile and adults of Litopenaeus setiferus collected from a field survey at the Natural Protected Area of Terminos lagoon, southern Mexico. The objective of the present approach was to determine if sampling site and/or shrimp age were contributing risk factors for disease between juvenile and adult shrimp; if there was a determined period of time in a year cycle when diseases were more critical, and if the analysis would help to decision‐ making considering what population would pose less risk of disease‐carrying when withdrawn for experimental purposes; all under an after‐the‐fact (ex‐post facto) approach. We identified that juvenile shrimp were at more risk of contracting some diseases in the estuarine environment and June, July and August months, were found to be a critical period when colonizing and parasitic diseases maintained a significant high prevalence in the shrimp population. These assumptions may help for decision‐making when wild shrimp have to be withdrawn from their natural environment for research purposes.